Apakah Kelebihan Kekasihmu dari Pada Kekasih Yang Lain? Kajian Hermeneutik Kritik Historis Kidung Agung 5:9–6:3 Dan Maknanya Bagi Jemaat Gmim “Firdaus” Tamara Wilayah Mapanget Tiga - Masambe, Helen; Sumolang, Easter Meini (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
Love is a feeling that unites relationships between people and even with God. Many people misunderstand this poem, and consider the contents of the Song of Songs to be vulgar, and only have sexual values between men and God, vulgar, and only has the value of sexuality between men and women.This thesis discusses the relationship of love in the text of Song of Songs 5:9-6:3 by using qualitative research methods through Hermeneutic Studies of Historical Criticism. The results The results of the research show the love relationship between the Israel and the Lord God, that perfect love only comes from God.